One Monetary Policy and Eighteen Central Bankers: The European Monetary Policy as a Game of Strategic Delegation - Rasmus Fatum (University of Copenhagen, Economic Policy Research Unit (EPRU), 2003)
This paper employs a multi-country delegation model of a single monetary policy and argues that a decision making mechanism based on the median voter theorem is too restrictive for capturing important aspects of monetary policy in the European Monetary Union, particularly because intensity of preferences cannot play a role when only the median voter matters. Replacing the median voter mechanism by a less restrictive weighted mean mechanism, it is shown that strategic delegation leads to a single monetary policy set in accordance with the preferences of the most inflation-averse member state. This finding provides theoretical support for The Twin Sister Hypothesis and the perception of the European Central Bank implementing the policy of the Bundesbank rather than the policy of an average union-wide central bank.
Keywords: C72; D72; E58; F33; 330; monetary policy; monetary union; median voter; strategic delegation; Geldpolitik; Eurozone; Medianwähler-Modell